Regular Physical Activity Can Prevent the Oncogenic Effects of Lifestyle-Associated Advanced Glycation End Products. (29th May 2020) - Krisanits, Bradley; Woods, Pamela; Nogueira, Lourdes; Spruill, Laura; Ford, Marvella; Findlay, Victoria; Turner, David
Abstract: Objectives: Lifestyle factors such as a sedentary lifestyle, obesity and a diet consisting of foods high in protein, fat, and highly processed foods contribute to the accumulation of advanced glycation end products (AGEs). AGE pathogenic effects are mediated through modification of protein function, genetic fidelity, stress responses, and cellular signaling pathways which can promote the development of a variety of chronic diseases. However, a gap in the literature exists on the role of dietary AGE in cancer progression and the potential impact of physical activity (PA) to negate such effects. Given the links between lifestyle and AGEs, we propose that a diet high in AGEs can accelerate prostate cancer progression and can be reversed by PA. Methods: Xenograft and spontaneous prostate cancer mouse models were utilized to assess the effects of dietary AGE on prostate tumor growth. Mice were exposed to PA on an Animal Treadmill for 1 hr, 5 days a week to assess the impact on dietary AGE mediated tumor progression. Tumor and prostate tissue were collected for histology, and Western Blot analysis. PBMCs were isolated from endpoint blood draws for flow cytometric analysis. Results: We found that chronic consumption of AGEs leads to a 3-fold increase in tumor growth in xenograft mice, accompanied by decreased expression of AR, increased expression of MYC, RAGE, and AGE as well as cell proliferation. In the spontaneous prostate cancer model chronic consumption of AGE resulted in increased progression towards high grade PIN and carcinoma when compared to l mice. IHC showed that the high AGE fed mice had increased recruitment of macrophages to PIN lesions. Mice in the PA arm showed a decrease in tumor growth (xenograft) and delayed progression (spontaneous). This was observed in all diet groups, but was most significant in the dietary AGE mice. Conclusions: Our studies support the concept that AGEs represent a biological consequence of lifestyle factors that promote cancer progression, and that PA may alleviate these effects. This may have the greatest impact in African American populations who have worse outcomes in prostate cancer, and where a lack of PA, poor diet, and high obesity rates are more prevalent. Funding Sources: Bradley Krisanits was supported by Hollings Cancer Center Pre-Doctoral Fellowship (MUSC), Graduate Assistance in Areas of National Need (US Dept. of Ed.), and U54 CA21096.